"It's Pronounced Imgur." : A Content Analysis on the Status and Logico-Semantic Relations between Imgur's Front Page Posts and the Top Comments - Kaarento, Auriina (My University, 2020)
Previous linguistic research has been conducted on Imgur.com, an image-sharing and hosting site, but they have either drawn conclusions from the comments or the Imgur users. This thesis is the first study to analyse the relation between popular Imgur comments and their posts. It also studies how applicable the selected theory is for this kind of data. 450 Imgur top comments were manually analysed using the image-text relation system by Martinec and Salway. The analysis is both quantitative and qualitative. The findings suggest that the status relation in this type of data is most likely unequal in a way that the text is subordinate to the image. The rest of the cases are either equal independent or equal complementary. There are eight different logico-semantic relations realised in the data, of which exemplification, text more general is clearly the most frequent. There are 17 ways of how the status and logico-semantic relations combine, of which most are formed between unequal status and the logico-semantic relation of exemplification, text more general. Because there are these certain status and logico-semantic category majorities, this could be seen as a pattern that most popular Imgur comments follow, even though there is diversity as well. Martinec and Salway’s system is found applicable for analysing hypermedia but it is unable to cover all the features of data this complex. Hence, I recommend that systems analysing image-text relations should be updated in order to respond to the requirements of hypermedia.
Keywords: hypermedia, social media, entertainment, digital discourse analysis, register analysis, image analysis